Effects of carvacrol, alfa pinene and cineole-rich essential oil mixed on performance, egg production and quality and egg lipid peroxidation in laying quails - Aziz Bulbul; Elmas Ulutas¹; Vural Ozdemir; Tuba Bulbul (Eurasian Journal of Veterinary Sciences)
Aim: The present study was conducted to determine the effects of essential oil mixtures rich in carvacrol, alpha-pinene and cineole supplementation in laying quail diets on performance, egg quality, and egg lipid peroxidation. Materials and Methods: A total of 420 (280 females and 140 males) eight-week-old Japanese quails (Coturnix coturnix japonica) were used. They were divided into 1 control group and 6 treatment groups containing 60 quails in each. Each group was divided into four replicate groups each containing 15 quails. The control group was fed basal diet. The diets of treatment groups occurring from carvacrol (C), alpha-pinene (P) and cineole (Cn) were supplemented with 100 and 1000 mg/kg essential oil mixed. The experimental period was lasted for 8 weeks. Results: The results showed that feed consumption decreased in the P1000 and Cn1000 groups (P<0.01). Feed conversion ratio was improved in the C1000, P1000 and Cn1000 groups (p<0.001). The egg yolk malondialdehid level during storage periods decreased in the P1000 group on the 15th day (P<0.05) and in the C100, C1000 and P1000 groups on the 30th day (P<0.001) compared with the control group. Conclusions: It was concluded that essential oil mixed supplementation rich in carvacrol or alpha-pinene can be used in laying quail diets because of these might be positive effect on feed conversion and the egg lipid peroxidation during storage periods.